Pediatric Scalp Burns: Hair Today, Gone Tomorrow?. Issue 2 (March 2015) - Menon, Seema; Jacques, Madeleine; Harvey, John G.; Holland, Andrew J. A.
Abstract : Scalp burns in the pediatric population appear relatively uncommon, with most reported cases occurring in adults secondary to electrical burns. We reviewed our experience with the management of these injuries in children. A retrospective review was conducted at our institution from March 2004 to July 2011. Scalp burns were defined as any burn crossing over the hairline into the scalp region. During the 7-year 4-month study, there were 107 scalp burns, representing 1.8% of the 6074 burns treated at our institution during that time. The cause was scald in 97, contact in 4, flame in 3, friction in 2, and chemical in 1. The majority (n = 93, 87%) appeared superficial to mid-dermal, with an average time to complete healing of 10.3 days. The remaining 14 cases (13%) were mid-dermal to full thickness, with an average time to complete healing of 50.8 days. Grafting was required in 12 cases (11%). The mean time to grafting was 4 weeks (range, 2 weeks to 2.5 months). The main complication of scalp burns was alopecia, which occurred in all grafted sites as well as in 4 patients treated conservatively. There were no other complications after grafting and no cases of graft loss. In our pediatric series, scalp burns were most commonly caused by scald injuries and were superficial to mid-dermal in depth. These generally healed rapidly but occasionally resulted in alopecia. The management of deep dermal and full-thickness scalp burns remains challenging in children, with the decision to graft often delayed.